The influence of curcumin additives on the viability of probiotic bacteria, antibacterial activity against pathogenic microorganisms, and quality indicators of low-fat yogurt - Buniowska-Olejnik, Magdalena; Urbański, Jakub; Mykhalevych, Artur; Bieganowski, Pawel; Znamirowska-Piotrowska, Agata; Kačániová, Miroslava; Banach, Maciej (Frontiers in Nutrition, 2023)
Curcumin is a nutraceutical with unique anti-inflammatory, anti-oxidative but also antimicrobial properties. In this study we aimed to examine the advantages of the use of water dispersible and highly bioavailable form of standardized turmeric extract (Curcuma longa L.) - NOMICU® L-100 (N) in the formulation of probiotic yogurt in comparison with the standard turmeric extract (TE). The antimicrobial activity of both supplements was studied and compared in the context of gram-positive and gram-negative bacteria, yeasts, and fungi. The N maintains the level of Bifidobacterium animalis subsp. lactis BB-12 in yogurt at the recommended level (7-9 log CFU/g) throughout the storage period. NOMICU® L-100 has also a higher inhibitory capacity for the growth of yeast and fungi. The evaluation of quality indicators of yogurt with N and TE at the level of 0.2% proves that yogurt with N has original taste properties. A lower degree of syneresis was noted for yogurt with TE (0.2%), but its sensory properties are unacceptable to the consumer due to the appearance of a bitter taste. In conclusions, based on the obtained results it has been proven that the use of NOMICU® L-100 (0.2%) in the composition of yogurt provides a product of functional direction with stable quality and safety indicators, which can be stored for at least 28 days